Sensor-integrated hip and knee prostheses: advances, challenges, and future perspectives - Wu, Xiang-Dong; Zhao, Zhixiong; Lu, Da; Shao, Hongyi; Yang, Dejin; Zhou, Yixin (Frontiers in Bioengineering and Biotechnology, 2026)
Total joint arthroplasty consistently alleviates pain and improves function in patients with end-stage joint disease. Nevertheless, up to 10% of hip and 20% of knee recipients remain dissatisfied after surgery, and registry data indicate that approximately one in five implants requires revision within 25 years, most commonly due to aseptic loosening, mechanical instability, or periprosthetic joint infection. Conventional postoperative surveillance relies on intermittent clinic visits and imaging, leaving a critical blind spot in our understanding of implant performance during daily activities. To address this gap, research has turned to fully implantable smart prostheses, such as hip and knee implants, embedded with sensors and low-power wireless telemetry that enable real-time monitoring of in vivo conditions. This review traces the evolution from early instrumented prototypes to the first commercially available smart knee; outlines enabling technologies, including sensing, communication, powering, and system integration; and summarizes clinical applications and early human data across this development continuum. Smart implants capture objective in vivo parameters that are not accessible to routine follow-up, including joint loads, range of motion, spatiotemporal gait metrics, and temperature, thereby enabling orthopedic phenotyping through dynamic, longitudinal digital representations of recovery trajectories and complication patterns. Fully implantable smart prostheses have the potential to shift arthroplasty toward continuous remote monitoring and proactive, precision follow-up care. Coupled with robust clinical decision-support systems and rigorous long-term evaluation, these technologies may usher in a new era of intelligent joint arthroplasty, with the potential to improve outcomes and extend implant longevity.